RELIGIÃO, COLONIALISMO E ALTERIDADE EM ROGER WILLIAMS - Barbosa, Adriel Moreira (2016)
This Master's Thesis presents the research results on Roger Williams – a english puritan pastor, who migrated to America to participate in the constitution of the Massachusetts colony in the year 1631. The question this research is on the reasons of Roger Williams for questioning the dominant thinking, on the nature of the Amerindian and the legitimacy of the occupation of their land. It starts with the thesis that from the experiences of Roger Williams, first with the suffering of the poor and with the religious persecution in England, along with his experiences in America, it was possible to contemplate the Amerindians as victims of English-puritan colonial system. Thus, the determinate objective was to analyze the criticism of Roger Williams to British colonialism and its defense of the Amerindians, seeking to understand it on the horizon of alterity of the Amerindians. This is a literature research of the author's works in which the Amerindian question appears and also that academic research related to the topic. For this, we refer us to the thought of Enrique Dussel, mainly through some categories of Liberation Philosophy, as Totality, Exteriority, Alterity, Alienation, Domination and Liberation, which enable think the colonial system in its inability to contemplate the amerindian externality. Also in Dussel, applied your reflection on the ethical criticism about the "negativity of the victims", in order to analyze this character's behavior in the face of colonial violence. And for the discussion about subjectness in Roger Williams, we seek the contribution of Franz J. Hinkelammert, on the subject of the theory. As a result, the three chapters of the text presents, respectively, a biographical and contextual synthesis of the character, followed by an exhibition of the debate on humanity and civility of the Amerindians and the issue of land and, in the third chapter, a discussion of Roger Williams and otherness. Was detected in the trajectory of the character who a ethical sensibility that led to the defense of socially marginalized groups, first in England and then in the colonies. Consequently, it was concluded that the defense of Amerindians followed the same criteria, allowing Williams to distance itself from European assumptions regarding its superiority to seek new paradigms about the relations between settlers and natives. It is hoped that this work can contribute to the critical reflections on the genesis of colonialism and of the first signs of critical thinking within the colonial system.